Analytic Subclass Conditions for Operators Involving the Generalized Imaginary Error Function (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we establish necessary and sufficient criteria for the generalized imaginary error function ϖin (z) to belong to the class F(ℏ1, ℏ2). We also derive an inclusion relation between the classes Gτ (A1,A2) and F(ℏ1, ℏ2). Furthermore, we provide a necessary and sufficient condition for the integral operator Gim(z) to lie in the class F(ℏ1, ℏ2).
Keywords: Analytic,; Univalent; Error function